Digitalisation and customer engagement in fast-food SMEs: enhancing brand presence through social media - Hajar Fatorachian; Ericka Arboleda; Thi Thuy Linh (Cogent Business & Management)
This study investigates how Small and Medium-sized Enterprises (SMEs) in the fast-food sector can enhance customer engagement and brand loyalty through effective social media strategies. Using a customer survey focused on Company A as a case study, the research examines consumer behaviour, preferences, and responses to the brand’s social media content. Drawing on theories from organizational learning, strategic management, organizational behaviour, and change management, the study emphasizes the role of Firm-Generated Content (FGC) in influencing consumer behaviour and brand perception, focusing on visually compelling and interactive content. The findings indicate that while paid advertisements are effective for short-term visibility, fast-food SMEs face challenges in sustaining organic engagement, which is crucial for building lasting customer relationships. Instagram® (social platform) emerges as the most effective platform due to its visual and interactive features, while Facebook® (social platform) shows a decline in engagement, particularly among younger users. The study also highlights the value of User-Generated Content (UGC) in boosting brand authenticity and organic reach, while stressing the importance of consistent brand messaging to maintain consumer trust. It addresses SMEs’ ethical responsibilities, including transparency and the promotion of healthier choices. Overall, it offers fresh insights into balancing paid and organic content through strategic engagement.